Peningkatan Kompetensi Kreatif Laboratorium Manajemen Aset Politeknik Negeri Bandung sebagai Unit Usaha Bidang Pengelolaan Aset - Tri Setyowati; Katharina Priyatiningsih; Nurlaila Fadjarwati (Prosiding Industrial Research Workshop and National Seminar, 2019)
Competence is a description of capabilities that include knowledge, skills and attitudes in order to get a certain job positions, including also the asset manager. The existence of Asset Management Laboratory at Polban is featured for vocational colleges. The needs for asset management through training and certification is constantly evolving and the role of Asset Management Laboratory as a business unit continued to improve its competence, by measuring the existing competencies and the needs of the industry. This study uses descriptive and confirmative with the object of the research to be carried out in Asset Management Laboratory Sampling for the entire project was conducted in stratified sampling with respondents involved is lecturer of the course. The results of a study reported that competencies Asset Management which has owned Laboratory Asset Management to carry out training and certification with five sub-competencies that an inventory, acquisitions, valuation, operating, and the maintenance of assets is already fulfilled 12 indicators from the 27 indicators measured, so there are 15 indicators that require efforts to increase competence, which push Laboratory Asset Management as TUK (The Competency Test) and as a Business Unit Asset Management Division.